2000
DOI: 10.1034/j.1600-051x.2000.027010787.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease status during pregnancy and 3 months post‐partum, in a rural population of Sri‐Lankan women

Abstract: The results of this study show that pregnancy had an effect only on the gingivae and not on periodontal attachment levels. The effects of oestrogen and progesterone could give rise to a more florid response to the irritant effects of plaque, resulting in severe gingivitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
144
1
16

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(185 citation statements)
references
References 18 publications
19
144
1
16
Order By: Relevance
“…Results of the study conducted by Pentapati et al, 9 Merglova et al, 10 Piscoya et al, 11 and Dhaliwal et al 12 also showed that gingival bleeding and periodontal pockets were significant problems reported by a large section of the expectant mothers. However, in the study conducted by Merglova et al, 10 only 9.8% of the pregnant women had periodontal pockets, whereas in the study conducted by Tilakaratne et al, 13 pregnancy had an effect only on the gingival and not on the periodontal attachment level. In the present study, 29.46% of the pregnant women had periodontal pockets.…”
Section: Discussionmentioning
confidence: 57%
“…Results of the study conducted by Pentapati et al, 9 Merglova et al, 10 Piscoya et al, 11 and Dhaliwal et al 12 also showed that gingival bleeding and periodontal pockets were significant problems reported by a large section of the expectant mothers. However, in the study conducted by Merglova et al, 10 only 9.8% of the pregnant women had periodontal pockets, whereas in the study conducted by Tilakaratne et al, 13 pregnancy had an effect only on the gingival and not on the periodontal attachment level. In the present study, 29.46% of the pregnant women had periodontal pockets.…”
Section: Discussionmentioning
confidence: 57%
“…Since the total time spent at the hospital after admission for most of the study participants did not exceed 40 days in relation to the time of the clinical examination for the plaque and gingival conditions (30), it is considered that this did not affect the results as gingival recession takes years to develop (19). However, the association between gingival bleeding on probing and recession in this study might have been exaggerated because of the tendency for having increased gingival bleeding during pregnancy and after delivery which takes time up to two or three months to resolve (31,32).…”
Section: Discussionmentioning
confidence: 95%
“…The primary role of microbial plaque in initiating gingivitis and periodontal destruction is well established. While examining other contributory factors such as the effects of hormonal flux in pregnancy on periodontal disease status, it is mandatory to isolate the effects of plaque (Tilakaratne et al, 2000).…”
Section: Discussionmentioning
confidence: 99%